Human-Wildlife Conflict: Issues Versus Mitigation - Anwar, Raheel; Saralch, Harmeet Singh; Kumar, Ashok (Indian Forester, 2015)
Human-wildlife conflicts have been in existence as long as wild animals and people shared the same landscape and resources. However, in the past two-three decades the conflicts have increased and become a growing concern for wildlife conservation in India. In this review, a study of current scientific literature addressing concerns for human safety and wildlife conservation have been evaluated to put forth the statements about the frequencies and causes of attacks based on findings concerning, existing data on the number of attacks by wild animals in India and information systems documenting causes and consequences of attacks. Research that provides credible information for wildlife management and advice for reducing the level of an encounter with wild animals and to minimize the livelihood of being attacked has also been documented. Need of a appropriate land use planning, public awareness, sustainable management of wildlife habitat, improving rural livelihood, counterbalance of losses with benefits, addressing public grievances, share and care of natural resources by rural communities, enhancing peaceful coexistence, low impact community-based ecotourism, etc could suitably help in resolving the growing concerns of Human-wildlife conflict in India.